The role of satisfaction as a mediator on the relationships between usage intention and word of mouth of Islamic bank products and their determinants - Abdul Rahman, Maria; Ramli, Mona Fairuz; Chauhan, Ajay (Universiti Teknologi Malaysia, 2019)
Islamıc banks have to become customer centric, if they have to remain competitive in the banking system. The banks need to understand factors that influence word of mouth and customer usage intentions towards their products. Studies that has been conducted to investigate customer word of mouth and usage intentions toward Islamic banking products are limited, and therefore this research is conducted to fulfill the gap. Data were collected from 245 respondents using structured questionnaire and were analysed for descriptive statistics using SPSS. Hypotheses testing were conducted through the use of Partial Least Squares (PLS). Findings of the study showed perceived value significantly influenced satisfaction, word of mouth and customer usage intentions toward Islamic Banking products. However, reputation only significantly influenced satisfaction and word of mouth toward Islamic Banking products. In addition, satisfaction was found to significantly mediate the relationships between reputation and word of mouth, and between perceived value and word of mouth. The information from this study is crucial to Islamic bank managers as it will assist them to develop strategies to attract more customers to use Islamic Banking products, without neglecting word of mouth. In the future, more variables should be considered in determining the customer usage intentions towards Islamic banking products.